2004
DOI: 10.1292/jvms.66.871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Central Kalimantan Plant Extracts on Intraerythrocytic Babesia gibsoni in Culture

Abstract: ABSTRACT. The inhibitory effects of 45 plant extracts selected from Central Kalimantan, Indonesia on Babesia gibsoni in vitro and their acute toxicity to mice were evaluated. Of these plant extracts studied, Arcangelisia flava, Curcuma zedoaria, Garcinia benthamiana, Lansium domesticum and Peronema canescens were found to have appreciable antibabesial activity with IC 50 values from 5.3 to 49.3 µg/ml without acute toxicity in mice at the intraperitoneal dose of 0.7 g/kg of body weight.KEY WORDS: antibabesial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…50 The antiplasmodial activity of a natural product has to be balanced by low cytotoxicity. In the present study, an IC value of 43.8±3.5 μg/ml [14]. Other research has also indicated that aqueous extracts from various plants show antibacterial and antiplasmodial activity [8].…”
Section: The Ic50supporting
confidence: 67%
See 1 more Smart Citation
“…50 The antiplasmodial activity of a natural product has to be balanced by low cytotoxicity. In the present study, an IC value of 43.8±3.5 μg/ml [14]. Other research has also indicated that aqueous extracts from various plants show antibacterial and antiplasmodial activity [8].…”
Section: The Ic50supporting
confidence: 67%
“…One previous study reported that a sungkai leaf extract showed in vivo antiplasmodial activity in Swiss mice [13]. Other studies published in 2004 and 2005 showed that sungkai leaf extracts had in vitro antibabesia activity [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of the antiprotozoal drugs, such as diminazene diaceturate, pentamidine isethionate, and parvaquone decreases the mortality in dogs [5,6]; however, they sometimes induce severe side effects [13]. One possible source of affordable treatment lies in the use of plant extracts and medicinal plants for the treatment of dogs infected with B. gibsoni [10].…”
mentioning
confidence: 99%
“…The combined water extracts were concentrated under reduced pressure and then freeze-dried into a powder. An aliquot of the sample (1 mg) was used for the antimalarial and antibabesial activity tests according to the reported methods [9][10][11]. The final concentration of each extract was 1 mg/ml for both assays.…”
mentioning
confidence: 99%
“…1) is one of the biflavonoids isolated from the leaves of Garcinia gardneriana (Botta et al, 1984). This compound is also found in other species such as Garcinia benthamiana, Garcinia brasiliensis, Garcinia madrunno (Botta et al, 1984), Rhus succedanea and Garcinia multiflora (Lin et al, 1997), which are associated with pharmacological effects such as anti-inflammatory, antinociceptive, antibacterial and antiparasitic (Subeki et al, 2004;Verdi et al, 2004;Castardo et al, 2008;Otuki et al, 2011;Melo et al, 2014). GB-2a per se has shown anti-inflammatory activity in two different animal models and moderate in vitro antiviral activity (Castardo et al, 2008;Otuki et al, 2011;Lin et al, 1997).…”
mentioning
confidence: 99%